Determinants of acute malnutrition among 6–59 months old children in public hospitals in Gambella town, Southwest Ethiopia: unmatched case-control study - Gesese, Abreha Addis; Khot, Luel Duoth (Frontiers in Nutrition, 2023)
Background: Acute malnutrition is a severe public health issue caused by poor nutrition over a short period of time. It is a powerful predictor of mortality. The Gambella region's risk factors for acute malnutrition, however, are not well understood. Thus, the risk factors for acute malnutrition were identified in this study.Methods: A facility-based unmatched-case control study design was conducted in public hospitals in Gambella town from February 15 to March 30, 2019. A total of 85 cases and 170 controls were included in the study. According to the average monthly caseload, children between the ages of 6 and 59 months were distributed among the public hospitals. Then, cases and controls were chosen using a systematic random sampling technique. A standardized, previously tested questionnaire was used to collect the data. EPI-data version 3.1 was used to enter the data, which was subsequently exported to SPSS version 20 for analysis. Statistical significance was set at p 0.05 for the bivariate and multivariable logistic regressions that were employed. Results: Household income of <=1500 birr (AOR = 2.46 at 95% CI (1.37-4.39)), being unemployed (AOR = 2.37 at 95% CI (1.34-4.20)), rural residence (AOR = 1.96 at 95% CI (1.10-3.51)), having diarrhea (AOR = 2.47, 95% CI (1.36-4.51)), fever (AOR = 2.05, 95% CI (1.03-4.10)), and pneumonia (AOR = 2.41), and exclusive breast feeding (AOR = 1.96, and exclusive breast feeding (AOR = 1.96, 95% CI (1.18-4.91)), and exclusive breast feeding (AOR = 1.96, ), minimum dietary diversity (AOR = 2.86, 95% CI (1.06-3.64)), minimum dietary diversity (AOR = 2.86, 95% CI (1.37-5.95)), weight measurement at birth (AOR = 0.86, 95% CI (0.08-0.93)), unplanned birth of the child (AOR=1.97, 95% CI (1.02-3.78), and non-immunized (AOR = 4.12, 95% CI (1.05-16.13)) were some of the main risk factors of acute malnutrition Conclusions: This research identified multiple risk factors for acute malnutrition in children aged 6-59 months, suggesting health interventions, and programs at all levels of the system executed in an organized manner with substantial program ramifications.